2022
DOI: 10.3390/su141710873
|View full text |Cite
|
Sign up to set email alerts
|

Slope Deformation Prediction Based on MT-InSAR and Fbprophet for Deep Excavation Section of South–North Water Transfer Project

Abstract: In the operation and maintenance of the South–North Water Transfer Project, monitoring and predicting the canal slope deformation quickly and efficiently is one of the urgent problems to be solved. To predict the slope deformation of the deep excavated canal section at the head of the canal. We propose a new idea of adopting the joint prediction of MT-InSAR and Fbprophet. Firstly, MT-InSAR monitoring technology was used to invert channel deformation using 88 Sentinel-1A orbit-raising image data with a time bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…4 . When interfering, filtering, and untangling the generated image pairs, the classical frequency domain rate filtering algorithm Goldstein method [ 33 , 34 ] was used for filtering and the Minimum Cost Flow (MCF) method [ 35 , 36 ] was chosen for untangling, and it was found that the best result was achieved when the threshold value of the untangling correlation coefficient was set to 0.35. The ground control points were obtained using the second detection method for orbit refinement, re-de-platforming, and two inversions.…”
Section: Methodsmentioning
confidence: 99%
“…4 . When interfering, filtering, and untangling the generated image pairs, the classical frequency domain rate filtering algorithm Goldstein method [ 33 , 34 ] was used for filtering and the Minimum Cost Flow (MCF) method [ 35 , 36 ] was chosen for untangling, and it was found that the best result was achieved when the threshold value of the untangling correlation coefficient was set to 0.35. The ground control points were obtained using the second detection method for orbit refinement, re-de-platforming, and two inversions.…”
Section: Methodsmentioning
confidence: 99%
“…The VMD-SSA-LSTM time prediction model combines the advantages of VMD, SSA, and LSTM techniques. It decomposes the original data using VMD, optimizes the LSTM model using SSA, and finally uses LSTM for prediction [27,30] . This combined model exhibits high prediction accuracy and flexibility in handling complex time series data.…”
Section: Multivariate Neural Network Prediction Modelmentioning
confidence: 99%
“…[34] designed to handle time series data. It introduces gating mechanisms (such as forget gates, input gates, and output gates) to address the issues of gradient vanishing and gradient explosion in traditional RNNs [27,35] .…”
Section: Multivariate Neural Network Prediction Modelmentioning
confidence: 99%
See 1 more Smart Citation